2021
DOI: 10.3390/ijms22052618
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Properties of Atopic Dermatitis-Associated Alopecia Areata

Abstract: Alopecia areata (AA) is regarded as a tissue-specific and cell-mediated autoimmune disorder. Regarding the cytokine balance, AA has been considered a type 1 inflammatory disease. On the other hand, AA often complicates atopic dermatitis (AD) and AD is regarded as type 2 inflammatory disease. However, the immunological aspects of AA in relation to AD are still poorly understood. Therefore, we aim to clarify the immunological properties of AD-associated AA. In this study, we performed comparative analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 49 publications
1
40
1
4
Order By: Relevance
“…While the mechanism of action of dupilumab in AA remains unknown, it has been hypothesized that some patients with AA and AD may exhibit more Th2 skewing. 10,11 Prior reports have suggested that those with more severe and long-standing AD may be more likely to experience hair regrowth with dupilumab; however, that is not a trend that we observed. 6,10 Additional studies will be necessary…”
Section: Discussioncontrasting
confidence: 73%
“…While the mechanism of action of dupilumab in AA remains unknown, it has been hypothesized that some patients with AA and AD may exhibit more Th2 skewing. 10,11 Prior reports have suggested that those with more severe and long-standing AD may be more likely to experience hair regrowth with dupilumab; however, that is not a trend that we observed. 6,10 Additional studies will be necessary…”
Section: Discussioncontrasting
confidence: 73%
“…4 Recent findings suggest that AA is involved in not only the Th1-driven process but also the Th2 pathway, especially in extrinsic AD patients. 5 Dupilumab, an inteleukin (IL)-4Ra antibody, improved concomittant AA in some AD patients, whereas AA developed after initiating dupilumab in others. Since…”
Section: Baricitinib Improved Alopecia Areata Concomitant With Atopic Dermatitis: a Case Reportmentioning
confidence: 99%
“…In contrast, exacerbation of AA in dupilumab‐treated AD patients has also been reported, 135 thus the efficacy of dupilumab for AA remains controversial. The differences in the response to dupilumab in AA has been speculated to be associated with the characteristics of comorbid AD, intrinsic or extrinsic 52,136 . Kageyama et al 136 reported that dupilumab would be effective for AA patients with extrinsic AD, but not for those with intrinsic AD.…”
Section: Expected Treatment Modalitiesmentioning
confidence: 99%